REORIENTASI KEBIJAKAN LUAR NEGERI PEMERINTAH AMERIKA SERIKAT TERHADAP KERAJAAN ARAB SAUDI PADA KONFLIK YAMAN 2017-2022 - Chalid Syamy Ramadhan; Prihandono Wibowo (Journal Publicuho, 2025)
This research aims to analyse the reasons behind the shift in US foreign policy towards Saudi Arabia in the Yemen war. Saudi Arabia, as a country involved in the conflict, is attempting to eliminate the Yemeni Houthi militia group. The US has had changing foreign policies towards Saudi Arabia during the Yemen war. Starting from a policy that more supported Saudi involvement in the conflict by providing military and intelligence support, to the emergence of efforts to halt arms sales, and then to a policy that emphasises urging the cessation of Saudi involvement in Yemen through a ceasefire. The change in US government policy towards Saudi Arabia has been driven by external and internal factors, as well as the impact of leadership changes. This research will highlight US policies during the administrations of President Donald J. Trump and President Joe Biden, covering the period from 2017 to 2022. This research will use qualitative and explanatory approaches to examine the shifts in US foreign policy. Journals, media, and official statements from the US and Saudi governments will serve as data for the construction of this research.